The role of agriculture in reducing child undernutrition in Nigeria - Amare, Mulubrhan; Balana, Bedru; Ogunniyi, Adebayo (International Food Policy Research Institute, 2020)
This study examines the effect of agricultural productivity change on child nutritional outcomes in Nigeria. Using several waves of micro-level panel data from Nigeria, we first show that high temperature (heat stress) reduces agricultural productivity change. A one percent increase in high temperatures during the crop growth period result in a 4 percent decrease in agricultural productivity. More importantly, our analysis provides several important insights on the implications of agricultural productivity change for reducing child undernutrition. The results show that agricultural productivity growth has a positive effect on child nutritional outcomes, measured by child height-for-age and weight-for-age. The main channel through which agricultural productivity growth affects child nutritional outcomes is by increasing food production for own household consumption. This suggests that productivity-enhancing investments in the agricultural sector could have a direct impact on child nutritional outcomes among smallholder households in Nigeria. The results also show that agricultural productivity change has higher impact for households who have better access to markets and a higher educational level. Interventions and policies geared towards intensification of agricultural production need to be complemented with strategies for widening educational programs and improving farmers’ access to markets. to induce incentives for increased production.